Recent Patents on Thin Coal Seam Mining Equipment - Wang, Yanxiang; Yang, Daolong; Xing, Bangsheng; Zhao, Tingting; Sun, Zhiyi; Huang, Qianqian; Li, Qian (Recent Patents on Mechanical Engineering, 2020)
Background: China's thin and extremely thin coal seam resources are widely distributed and rich in reserves. These coal seams account for 20% of the recoverable reserves, with 9.83 billion tons of industrial reserves and 6.15 billion tons of recoverable reserves. Objective: Due to the complex geological conditions of the thin coal seam, the plow mining method cannot be effectively popularized, and the drum mining method is difficult to be popularized and applied in small and medium-sized coal mines, so it is necessary to find other more advantageous alternative mining methods. Methods: The equipment integrates mining operations, conveying operations, and supporting operations, and is suitable for mining short and extremely thin coal seam with a height of 0.35m-0.8m and width of 2m-20m. It has the advantages of the low body of the shearer, no additional support on the working face, and small underground space. The mining efficiency of thin coal seam and very thin coal seam can be improved and the mining cost can be reduced. Results: Thin coal seam shear mining combines mining, conveying, and supporting processes together and has the advantages of a low fuselage, no extra support required for the working face, and feasibility in a small underground space. Conclusion: The summarized mining method can improve the mining efficiency of thin and extremely thin coal seams, reduce mining costs, and incorporate green mining practices, which take both mining economy and safety into account.
Keywords: Coal mining